The Use of Trauma Healing in Treating PTSD in Post-Disaster Victims: A Narrative Review - Titin Sutini; Etika Emaliyawati; Siti Nurfazri Sodiqiah; Salwa Mawaddah; Fitri Yoselin Yamadea Purba; Agni Rizkiani; Dhiyaa Ulhaq Amatullah (STIKep PPNI Jawa Barat, 2022)
Aims: Natural disasters can have an impact on the material (physical), psychological and social aspects. The traumatic experience is a psychological impact on victims that are often found. traumatic experience or traumatic stress if it lasts for 6 months will result in PTSD (Post Traumatic Stress Disorder). There are various interventions to treat PTSD, this intervention is known as trauma healing. Trauma healing can be one of the appropriate rehabilitation tools for disaster victims, especially to heal post-disaster trauma. The purpose of the study is to find out what trauma healing interventions are in handling PTSD in post-disaster victims. Method: The method used is a narrative review with PRISMA 2009 guidelines. The search is based on Garuda, EBSCO, Proquest, and PubMed. The studies reviewed were RCT research, quasi-experiment, and qualitative research in English and Indonesian with full text, as well as intervention studies within the last 7 years of publication from 2015 to 2021. Result: Trauma healing that can be given and proven effective to treat or reduce PTSD symptoms is CBT (Cognitive Behavioral Therapy), remembrance therapy, dhikr and play therapy. The results of the search used turned out to be for CBT therapy and play therapy were more effective in reducing PTSD in children, while dhikr was effective in adults, and remembrance therapy was very suitable for adults who experienced PTSD with other physical problems such as hypertension. Conclusions: Therapy as post-disaster trauma healing to overcome PTSD is divided into two, namely therapy for children and adults. Therapy for children is playing therapy and CBT, while for adults there is dhikr, and remembrance therapy is used for adults who experience physical disorders such as hypertension.